The Effect of Listening to Dangdut Koplo Music on Increasing Worker Productivity at Al Firdaus Production in Trawas Village - Muhammad Ikhwan Zulfikar Fahmi (Repertoar, 2026)
This study analyzes the effect of listening to dangdut koplo music on increasing worker productivity at Al Firdaus Production in Mojokerto. The study was motivated by the phenomenon of work burnout caused by repetitive tasks that hinder the achievement of production targets. The theoretical framework used is Adam Smith’s Theory of Efficiency, which posits that work output is optimized in a conducive environment. The research method employed a simple experiment using a One-Group Pretest-Posttest design involving 11 respondents. Data were collected through observation, documentation, and in-depth interviews. The results showed that in the condition without music (pretest), average production was only 7.09 units/day (total of 78 pieces). After the dangdut koplo music intervention (posttest), average production increased significantly to 9.27 units/day (total of 102 pieces). Analysis indicated a 30.77% increase in productivity. Interview results confirmed that dangdut koplo music serves to lift mood and drive the work rhythm. The study’s conclusion demonstrates that dangdut koplo music significantly improves work efficiency by minimizing burnout without increasing working hours.